PENGARUH TINGKAT PENDIDIKAN DAN PENGHASILAN ORANG TUA TERHADAP PRESTASI BELAJAR SISWA KELAS VII PADA SMP NEGERI 7 DUMAI DI MASA PANDEMI COVID-19 - Supirman (UIR Press, 2022)
This research wants to see the influence’s of education degree and parent’s income to the student’s achievement in studying of seventh degree in SMP Negeri 7 Dumai in pandemic covid-19 era, This research uses the quantitative of reseach type which the theory of multiple linear regression which the purpose for to know how big is, the influence of education degree and parents’s income to studying achievement of 72 students in seventh degree in SMP Negeri 7 Duma in pandemic of Covid 19 era. Technique in taking the sample was done in proportionate stratified Random Sampling, used the slovin formula from 260 students. There are variabels in this research; the degree of parents education, the degree of parents income and the students studying achicvement. The collecting of data’s are by questioners and documentation, Instrument test was done with validity reliability test. The data analysis used percentage descriptive analysis and regresy analysis and multiple linear regression, the resulted there are lufluencing of education degree and parent’s income degree to the student’s achievement in studying. The result of this research suggested to the students always have the motivation in their education process to reach the maximal achievement in studying and students parents can give supporting and student’s need in education though in condition of education degree and low of income especially in pandemic Covid 19 era.